The Impact of COVID-19 on Preventive Oral Health Care During Wave One - Meyer, Beau D.; Danesh, David O. (Frontiers in Dental Medicine, 2021)
Introduction: Early childhood caries burdens children, their families, and the health care system. Utilizing fluoride varnish at medical well-child visits with non-dental primary care providers can be an interprofessional strategy to combat early childhood caries. The COVID-19 pandemic dramatically altered preventive health care delivery and the effects on preventive oral health care delivery have not been previously described. Methods: This analysis used descriptive statistics and non-parametric Wilcoxon Mann-Whitney tests to compare preventive oral health utilization among 1 to 5-year old children in two state Medicaid agencies before and during the pandemic. Fluoride utilization rates at dental visits and medical well-child visits were calculated as number of users per 1,000 enrolled children. Additionally, the proportion of well-child visits that included fluoride application was calculated for each state. Results: During the pandemic, the quarterly fluoride utilization rate significantly decreased at dental visits (pre-pandemic = 153.5 per 1,000 enrolled children; pandemic = 36.1 per 1,000 enrolled children, p < 0.001) and signficantly decreased at medical well-child visits (pre-pandemic = 72.2 per 1,000 enrolled children; pandemic = 32.3 per 1,000 enrolled children, p = 0.03) during the pandemic. Conclusions: The findings highlight the importance of interprofessional collaboration among non-dental primary care providers and dental providers to provide access to preventive oral health services, particularly when access to dentists is limited. Future directions might include rigorous evaluations of co-located medical and dental services or the use of interprofessional telehealth technologies.